O que pode um corpo? movimentos desejantes na educação infantil : experiências de afetos no encontro da dança com crianças e funcionários de um CMEI - Silva, Giovana Barbosa da (2013)
This research took place in a CMEI (Municipal Center for Early Childhood Education), in Vitória ES. It focused on cartographing/ following the movements of desire in the curriculum-thinking narratives crossed by agencements of bodies in dance, which mobilize the formation processes of Early Childhood Education in a CMEI. Such movements let us problematize what affection relations can do the (collective) body in the learning environment along trails of territorialization/deterritorialization dance. The research is composed by children s and professionals narratives among the dance movements that emerge in the CMEIs everyday life and also by the movement of the experience of mounting a musical play with the CMEI s professionals as a product of our meeting. Thus, we were allowed to pursue the ways in which the subjects mobilize the curriculum by the expression of desire, and question how they appropriate the experience of dancing to think the curriculum. Therefore, we emphasized the investigation of the contagious movement of bodies through dance. By doing so, we were able to realize the translations/updates in the curriculum that are produced by students and professionals from the CMEI. The research on stage, together with the children/ students and professionals of the CMEIs everyday life, revealed the variety of steps that choreograph the ballet of knowledge and practices which compose this education s curriculum. This imposes the need to put in evidence the alliances and inventions which emerge from the ways of being in school by means of effects of dance on the body, letting us notice, in the minuteness of the everyday life ballet, modes of affirmation of life, a curriculum that escapes the control of the instituted, and which is done in a potentially inventive, artistic, dancing, moving the desire, the thinking.